Endothelial dysfunction in adolescents and young adults with nonalcoholic liver disease - Cristiana G. Moise; Octavian Istrătoaie; Ionuț Donoiu; Edme R. Mustafa; Georgică C. Târtea; Diana R. Tudorașcu; Ion Rogoveanu (Journal of Mind and Medical Sciences)
Nonalcoholic liver disease is a global public health problem that increases cardiovascular morbidity and mortality in these patients. This paper discusses endothelial dysfunction among patients (adolescents and young adults) with nonalcoholic liver disease. On the one hand, evidence suggests that cardiovascular disease is the leading cause of mortality in patients with advanced nonalcoholic liver disease and that nonalcoholic fatty liver is associated with an increased risk of cardiovascular disease independent of the presence of cardiovascular risk factors and metabolic syndrome components. On the other hand, nonalcoholic liver disease, especially the non-inflammatory form of nonalcoholic steatohepatitis, may not only be a marker of cardiovascular damage but also a factor involved in its pathogenesis. Such patients are candidates not only for the treatment of liver disease but also for the early treatment of cardiovascular risk factors because many of them, especially those with severe nonalcoholic liver disease, will develop major cardiovascular events and may eventually die of cardiovascular disease before the advanced liver disease occurs.